As políticas de investimento, financiamento e dividendos, e os retornos das ações: evidência empírica para uma empresa brasileira do segmento de varejo, utilizando estudo de evento - Xavier, Moacir (2010)
The finance literature defines that stock prices are influenced mainly by the policies of funding, distribution of dividends / share buyback and investments, which are usually defined by financial managers. The objective of this research is to evaluate empirically whether these policies have a significant impact on pricing of the stock market. To achieve this goal it was decided to produce a case study for Cia. Brasileira de Distribuição inn which, trough an event study, we sought to determine the validity of the policies mentioned above in the light of events representative of those policies. Information about the events were collected and applied to the chosen methodology, which seeks to identify whether the market is efficient or not, depending on the information it receives and process. The tests were performed and identified that, for Cia Brasileira de Distribuição, only the investment policy has statistical significance for the market condition is not efficient, thus influencing the return of shares and the market value of the company. Tests of events representing the other two policies had resulted in the condition that the market is efficient, which means in the case of Cia Brasileira de Distribuição that both the policy of funding the dividend policy will not affect the abnormal return of its shares